2010 40th IEEE International Symposium on Multiple-Valued Logic 2010
DOI: 10.1109/ismvl.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

ESOP-Based Toffoli Network Generation with Transformations

Abstract: In this paper a new Toffoli gate cascade synthesis method is presented. This method is based on previous work and generates a cascade of inverted-control-Toffoli gates from the ESOP representation of a multi-output function. The algorithm first generates a circuit with n + m lines, where n and m are the number of inputs and outputs, respectively. A set of gate transformations are applied to the circuits to remove some of the output lines. The improvements of this new algorithm are twofold: most NOT gates are e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
1
22
0
Order By: Relevance
“…Although synthesis and optimization approaches which create circuits composed of negatively controlled Toffoli gates already exist (e.g. ESOP-based synthesis [16][17][18] or QMDD-based synthesis [19]), they often just exploited the structure of the respective function representation. More precisely, in ESOP-based synthesis, negative control lines are just applied as they allow for a straight-forward realization of negative literals.…”
Section: Motivation and General Ideamentioning
confidence: 99%
See 1 more Smart Citation
“…Although synthesis and optimization approaches which create circuits composed of negatively controlled Toffoli gates already exist (e.g. ESOP-based synthesis [16][17][18] or QMDD-based synthesis [19]), they often just exploited the structure of the respective function representation. More precisely, in ESOP-based synthesis, negative control lines are just applied as they allow for a straight-forward realization of negative literals.…”
Section: Motivation and General Ideamentioning
confidence: 99%
“…realizations obtained by various synthesis approaches. However, our evaluations showed that the proposed methodology is particularly suited for circuits derived by ESOP-based synthesis [16][17][18]. Here, the targets lines are usually assumed to be placed on certain output lines, while control lines are usually placed on the separate input lines.…”
Section: Algorithmmentioning
confidence: 99%
“…Several methods rely on the Exclusive Sum-of-Product (ESOP) form of the Boolean function [10], while a set of methods use repeated transformations on the Boolean function truth-table for performing reversible logic synthesis [12].…”
Section: B Reversible Logic Synthesismentioning
confidence: 99%
“…The approach described in [30,29,31] takes the best advantage of shared functionality if the ESOP terms are shared by only two outputs. However, if the shared terms exist in more than two outputs then transformation of each term may require more than one…”
Section: Post-synthesis Optimizationmentioning
confidence: 99%